The art of paradigm maintenance: how the New Keynesian 'Science of Monetary Policy' tries to deal with the inflation of 2021-2023 - Servaas Storm (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
The macroeconomic models used by major institutions including the Federal Reserve and the International Monetary Fund (IMF) failed to predict the inflation surge during 2021-2023. The output gap, the unemployment gap, the New Keynesian Phillips curve and inflation expectations did not give timely and relevant signals. The re-emergence of inflation thus threw the 'science of monetary policy' off the rails. Faced with the choice between changing their paradigm and proving that there is no need to do so, the 'scientists of monetary policy' got busy on the proof. As a result, a number of ad hoc epicycles have been added to the New Keynesian analytical core - with the help of which one can claim to be able to explain the sudden acceleration of inflation post factum. This paper critically reviews the theoretical and empirical merits of three recent tweaks to the New Keynesian core: using the vacancy ratio as the appropriate measure of real economic activity; hammering on the considerable risk of an imminent wage-price spiral; and the resurrection of the non-linear Phillips curve. The paper concludes by drawing out sobering lessons concerning the art of paradigm maintenance as practiced by the 'scientists of monetary policy'.
Keywords: E0; E5; E6; E62; I12; J08; O23; 330; Inflation; Inflation expectations; Non-linear Phillips curve; Output gap; Science of monetary policy; Unemployment gap; Vacancy ratio; Wage-price spiral